-2a+40+9a=3a-6a

Simple and best practice solution for -2a+40+9a=3a-6a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+40+9a=3a-6a equation:



-2a+40+9a=3a-6a
We move all terms to the left:
-2a+40+9a-(3a-6a)=0
We add all the numbers together, and all the variables
-2a+9a-(-3a)+40=0
We add all the numbers together, and all the variables
7a-(-3a)+40=0
We get rid of parentheses
7a+3a+40=0
We add all the numbers together, and all the variables
10a+40=0
We move all terms containing a to the left, all other terms to the right
10a=-40
a=-40/10
a=-4

See similar equations:

| 2x2=10 | | 8-2x-6-13x=5 | | 12x-97=119 | | X(x-4)-2=x2-4(x+3) | | x2−4x−3=0 | | 4(x+1)=6-x | | -5x+5=8-(5x+3) | | x²+10x-400=0 | | 6x/5-5=7 | | 6x/6-5=7 | | 3+7p=10 | | 10x-5x-4x=5 | | 20x-7=14x+5 | | (2x+3)(2x-3)=27 | | -1/2x(2/3x-3/4)-7/2x=-83/24 | | a+6/6=2 | | 42-x=x^2 | | 6i+2i=8i | | 9x-4+79=180 | | 4x1=30-2.5×2 | | 4x1=30-2.5×-2 | | s=V+1.05 | | 15=3x–3 | | (5x+7)^2=3 | | 90+(5x-13)+(2x+33)=180 | | 4x-9x+5=x-5+10 | | (2+2)(4×2x)=30-2.5(×+2) | | 33=7(1+2a) | | x*x*x=625x | | 10z=-100= | | -11=x+7= | | 5b+4=-41 |

Equations solver categories